2008
DOI: 10.1021/jm800093c
|View full text |Cite
|
Sign up to set email alerts
|

Trithiocarbonates as a Novel Class of HDAC Inhibitors: SAR Studies, Isoenzyme Selectivity, and Pharmacological Profiles

Abstract: Inhibitors of histone deacetylases (HDAC) are currently developed for the treatment of cancer. These include compounds with a sulfur containing head group like depsipeptide, alkylthiols, thiocarboxylates, and trithiocarbonates with a carbonyl group in the alpha-position. In the present investigation, we report on the synthesis and comprehensive SAR analysis of HDAC inhibitors bearing a tri- or dithiocarbonate motif. Such trithiocarbonates are readily accessible from either preformed or in situ prepared alpha-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 32 publications
0
26
0
Order By: Relevance
“…Compound 12ac (Figure 12) was described as a selective HDAC6 inhibitor of all compounds with trithiocarbonate, and compound 12ac with a phenylacetyl moiety as the CAP group displayed better selectivity for HDAC6 ( IC 50 of 65 nm) over HDAC1( IC 50 of 1.22 μM)in in vitro enzyme assays (55). The selective inhibition was also confi rmed with the result that tubulin hyperacetylation (10 μM) was stronger than that of histone 3 (55).…”
Section: Trithiocarbonatesmentioning
confidence: 73%
See 1 more Smart Citation
“…Compound 12ac (Figure 12) was described as a selective HDAC6 inhibitor of all compounds with trithiocarbonate, and compound 12ac with a phenylacetyl moiety as the CAP group displayed better selectivity for HDAC6 ( IC 50 of 65 nm) over HDAC1( IC 50 of 1.22 μM)in in vitro enzyme assays (55). The selective inhibition was also confi rmed with the result that tubulin hyperacetylation (10 μM) was stronger than that of histone 3 (55).…”
Section: Trithiocarbonatesmentioning
confidence: 73%
“…The selective inhibition was also confi rmed with the result that tubulin hyperacetylation (10 μM) was stronger than that of histone 3 (55). Compound 13 ( Figure 13) structurally characterized with a pyrrole-N-sulfonamide displayed an IC 50 of 9 nM for HDAC6 and an IC 50 of 2.1 μM for HDAC1 (55).…”
Section: Trithiocarbonatesmentioning
confidence: 99%
“…Similarly, Dehmel et al have recently identified certain trithiocarbonate derivatives (12ac) that are highly selective for HDAC6 3 while Itoh et al have identified certain thiolate derivatives (16b) that demonstrate similar selectivity for HDAC6. 4 Besides these selective HDAC6 inhibitors a number of broad spectrum HDAC inhibitors have been identified that inhibit other HDAC class I and II enzymes also.…”
Section: Dear Sirmentioning
confidence: 99%
“…Previously, Dehmel et al [10] used the intermediary 2 for the construction of trithiocarbonates as HDAC (Histone deacetylase) Inhibitors.…”
Section: General Informationmentioning
confidence: 99%